2021
DOI: 10.1111/ppc.13003
|View full text |Cite
|
Sign up to set email alerts
|

The effects of logotherapy on meaning in life, depression, hopelessness, and suicidal ideation, in patients with depression: An intervention study

Abstract: Purpose: To evaluate the efficacy of logotherapy on meaning in life, depression, hopelessness, and suicide ideation in patients with depression.Design and Methods: A quasi-experimental approach was used and 86 participants were recruited from a psychiatric department in Taiwan. The experimental group received logotherapy for 12 weeks. The control group received depression education as usual. Findings:The results revealed significant differences between and within the groups for meaning in life, depression, hop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 25 publications
1
31
0
Order By: Relevance
“…Regarding the effectiveness of MCP for meaning in life, although it was not the initial objective of this systematic review study, three quasi-experimental studies found that MCP was more effective than a control condition in improving meaning in life, with large effect sizes (Cho et al, 2013;Kim & Choi, 2020;Sun et al, 2021), and two studies indicated that the improvement was maintained at follow-ups (Cho et al, 2013;Kim & Choi, 2020). In the same way, regarding the effectiveness of MCP for reducing anxiety, one RCT study found that MCP was more effective than the control condition in reducing anxiety, with a small effect size (Delavari et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Regarding the effectiveness of MCP for meaning in life, although it was not the initial objective of this systematic review study, three quasi-experimental studies found that MCP was more effective than a control condition in improving meaning in life, with large effect sizes (Cho et al, 2013;Kim & Choi, 2020;Sun et al, 2021), and two studies indicated that the improvement was maintained at follow-ups (Cho et al, 2013;Kim & Choi, 2020). In the same way, regarding the effectiveness of MCP for reducing anxiety, one RCT study found that MCP was more effective than the control condition in reducing anxiety, with a small effect size (Delavari et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…In n = 4 (66.66%) studies, the intervention was MCP or logotherapy (Delavari et al, 2014;Kim & Choi, 2020;Moosavi et al, 2012;Sun et al, 2021), and in n = 2 (33.33%) studies, the intervention used was logo-autobiography (Bernstein et al, 2016;Cho et al, 2013).…”
Section: Intervention Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations